Organizational and technical environment of financial controlling in agricultural organizations - S. M. Bychkova; E. A. Zhidkova; D. V. Elyashev (Путеводитель предпринимателя, 2020)
The article describes the organizational and technical environmentfor controlling the finance ofan agricultural enterprisefrom the position ofstudying the controlling environment of the application of tetrad theory. The main problematic issues of organization of controlling at the enterprise are considered, taking into account the role of various stakeholders, the requirements for the technical implementation of the controlling system based on the use of modern information technologies and automated systems are disclosed.